Sludge conditioner and application thereof in treatment of organic biochemical sludge
The sludge conditioner made of Xinjielm, sodium hexametaphosphate and titanium modified tanninized chitosan has been solved by solving the problem of large dosage and low dehydration efficiency in the prior art, and has achieved efficient dehydration and low moisture content sludge treatment without secondary pollution risk.
Patent Information
- Application Number
- CN202411738535.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-29
AI Technical Summary
When treating organic biochemical sludge, the existing sludge conditioning agents have large doses, low dehydration efficiency, poor sedimentation performance, and are difficult to effectively remove biological intracellular fluid and intercellular water. The sludge moisture content is difficult to reduce, and there is a risk of secondary pollution.
The sludge conditioner made of Xinjielm, sodium hexametaphosphate and titanium modified tannin chitosan is used to modify cell membrane permeability, sodium hexametaphosphate destroys EPS structure, and titanium modified tannin chitosan improves dissolution and sedimentation performance, achieving efficient dehydration and low moisture content treatment of the sludge.
It effectively reduces the dosage of conditioner, improves the settlement performance and dehydration rate, and makes the treated sludge moisture content low and does not have the risk of secondary pollution.
Smart Images

Figure BDA0005162069950000021 
Figure BDA0005162069950000022 
Figure BDA0005162069950000041
Abstract
Description
Technical Field
[0001] The invention relates to a sludge conditioner and also to the application of the sludge conditioner in treating organic biochemical sludge. Background Art
[0002] The sludge produced by the sewage treatment plant is a collection of bacterial flocs formed by various microorganisms and adsorbed organic and inorganic substances. It has a special colloidal structure and high hydrophilicity, which leads to a large specific resistance (the larger the specific resistance, the worse the filtration performance of the sludge and the more difficult it is to dehydrate), and poor dehydration performance. In order to destroy the colloidal structure of the sludge and improve the dehydration performance of the sludge, the sludge needs to be conditioned. At present, the most widely used conditioning method in sewage treatment plants is chemical conditioning, which neutralizes the charge of the sludge colloidal particles by adding sludge chemical conditioning agents, thereby destroying the colloidal structure of the sludge, reducing its affinity with water, reducing specific resistance, making it easy to concentrate and filter, and thus reducing operational difficulties. Sludge conditioners are currently divided into two categories: inorganic sludge conditioners (such as PAC, calcium salts) and organic sludge conditioners (such as PAM). Although inorganic sludge conditioners have low costs, they are added in large amounts (accounting for 6-9wt‰ of the sludge volume), produce large amounts of sludge (accounting for 20-30wt% of the absolutely dry sludge), have low conditioning efficiency, slow settling rates of conditioned sludge aggregates, poor sludge resource utilization performance, and are prone to soil compaction and salinization when landfilled. Compared with inorganic sludge conditioners, organic flocculants have small addition amounts and excellent settling performance, but low dehydration efficiency and are unable to effectively remove biological intracellular fluid, intercellular water, and extracellular polymer bound water. They can only remove free water from the sludge, and the sludge moisture content can only be reduced to about 75-85%. At the same time, this type of conditioner is difficult to biodegrade, and acrylamide monomers and oligomers are prone to cause secondary pollution to the environment. Summary of the invention
[0003] Purpose of the invention: The purpose of the present invention is to provide a sludge conditioner, which can effectively reduce the dosage of the conditioner when treating organic biochemical sludge, and has excellent sedimentation performance and high dehydration rate, so that the moisture content of the treated sludge is low; another purpose of the present invention is to provide the use of the above-mentioned sludge conditioner in treating organic biochemical sludge.
[0004] Technical solution: The sludge conditioner of the present invention comprises the following components in parts by weight: 0.5-1 part of benzalkonium bromide (Sanisol), 0.5-1 part of sodium hexametaphosphate, 5-10 parts of titanium-modified tannin chitosan and 88-95 parts of water.
[0005] The titanium-modified tannin chitosan is prepared by the following method: mixing TiO2 nanoparticles with tannin chitosan solution, and then calcining at high temperature after mixing evenly to obtain titanium-modified tannin chitosan.
[0006] The concentration of the tannin chitosan solution is 0.05-0.2 g / L; the concentration of the TiO2 nanoparticles in the tannin chitosan solution is 0.1-1.0 g / L. The tannin chitosan obtained after tannic acid modification can greatly improve the solubility of chitosan in water, thereby obtaining a tannin chitosan solution.
[0007] The high temperature calcination temperature is 160-180°C, and the reaction time is 1-2h.
[0008] Wherein, tannin chitosan is prepared by the following method, and the method steps are as follows:
[0009] (1) Dissolve chitosan in acetic acid, stir evenly and adjust the pH to 6-7;
[0010] (2) at high temperature, adding benzaldehyde dropwise to the solution of step (1) to react; the role of benzaldehyde is to form a Schiff base with the amino group of chitosan. The Schiff base generated by the reaction is quite stable in a neutral environment and can protect the amino group on the chitosan from being reacted (not reacting with tannin). The Schiff base will be rapidly hydrolyzed in an acidic environment and restored to a free amino group;
[0011] (3) adding tannin to step (2) and mixing evenly;
[0012] (4) at high temperature, adding glyoxal to the mixed solution of step (3) to react; glyoxal can act as a cross-linking agent to graft tannins onto chitosan to modify it;
[0013] (5) Soaking the product after the reaction in hydrochloric acid, and drying it after soaking to obtain powdered tannin chitosan.
[0014] Wherein, in step (2) and step (4), the reaction temperature is 65-70°C and the reaction time is 2-3h.
[0015] Wherein, in step (3), the added mass ratio of chitosan to tannin is 1:1.
[0016] Wherein, in step (2) and step (4), the added mass ratio of benzaldehyde to chitosan is 1.5-2:1; the added mass ratio of glyoxal to chitosan is 1.5-2:1.
[0017] Wherein, in step (5), the drying temperature is 45-50° C. and the drying time is 22-24 hours.
[0018] The reaction principle of chitosan and tannin to form tannin chitosan:
[0019]
[0020] The reaction principle of tannin chitosan and TiO2 to prepare titanium-modified tannin chitosan:
[0021]
[0022] The chlorhexidine in the sludge conditioner of the present invention can change the permeability of the cell membrane, thereby denaturing the protein on the bacterial cell wall and the cell membrane, and by inhibiting the activity of key enzymes in the bacteria, the bacterial cell structure in the sludge is broken, and then the intracellular water in the sludge is released; sodium hexametaphosphate effectively destroys the extracellular polymer (EPS) structure and releases bound water through chelation, changing ionic strength, promoting hydrolysis, changing surface properties and physical destruction, so as to facilitate subsequent treatment; titanium-modified tannin chitosan is a high-performance amphiphilic synthesized product with chitosan and tannin as the main reaction raw materials. The molecular compound (tannin chitosan) has a large molecular weight of the amphoteric polymer obtained by cross-linking reaction, which can overcome the problem of incomplete flocculation caused by the small molecular weight of chitosan when used as a sludge conditioner. On the other hand, the introduction of polyphenolic hydroxyl and carboxyl groups of tannin into the chitosan molecule can effectively improve the solubility of chitosan (referring to the solubility of chitosan in water. The improvement of solubility is more conducive to the dispersion of sludge conditioners in the reaction system, making various reactions in the system more sufficient); in addition, loading titanium salt on tannin chitosan can greatly improve the sedimentation performance of the sludge conditioner.
[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant effects: the present invention utilizes chlorhexidine, sodium hexametaphosphate and titanium-modified tannin chitosan to prepare a high-efficiency sludge conditioner, which has a small dosage during use, excellent sedimentation performance, no secondary pollution, and a low moisture content in the treated sludge; and the conditioned sludge can be calcined at high temperature to regain TiO2 with high photocatalytic activity, thereby further reducing the cost of solid waste treatment. DETAILED DESCRIPTION
[0024] Example 1
[0025] The preparation method of the sludge conditioner of the present invention comprises the following steps:
[0026] (1) Preparation of tannin chitosan:
[0027] (1.1) Dissolve 0.2 g of chitosan in 50 mL of 0.5 M acetic acid, place in a stirring vessel and slowly stir at room temperature for 10 to 15 min until uniform;
[0028] (1.2) Add 30 wt% sodium hydroxide to the solution of step (1.1) and adjust the pH to 6-7 (adjusting the pH to 6-7 can make chitosan dissolve in the system without precipitation, and can make chitosan and benzaldehyde react more fully); adjust the temperature of the stirring tank to 65-70°C, and continuously add 0.3 g of benzaldehyde thereto and react for 2-3 hours;
[0029] (1.3) The solution of step (1.2) was placed in an oven at 45°C and dried to obtain a solid powder, which was redispersed in water, to which 0.2 g of tannin was added, and the mixture was placed in a stirred tank and slowly stirred at room temperature for 10 to 15 minutes until uniform;
[0030] (1.4) Add 0.3 g of glyoxal to the stirred tank, adjust the temperature of the stirred tank to 65-70°C, and react for 2-3 hours;
[0031] (1.5) placing the solution of step (1.4) in an oven at 45°C and drying to obtain a solid powder, and then soaking the solid powder in 5 mL of 30 wt% hydrochloric acid for 5 to 8 hours to remove the benzaldehyde that reacts with the chitosan during the soaking process, so that the amino groups of the chitosan are restored to free amino groups;
[0032] (1.6) placing the solution of step (1.5) in an oven at 45°C and drying for 24 hours to obtain powdered tannin chitosan;
[0033] (2) dissolving tannin chitosan in water to obtain a tannin chitosan solution with a concentration of 0.1 g / L;
[0034] (3) adding nano-TiO2 powder to the above-mentioned tannin chitosan solution with a concentration of 0.1 g / L, and after ultrasonic dispersion for 30 minutes, placing the mixed solution in a muffle furnace and reacting at 170° C. for 1.5 hours to obtain titanium-modified tannin chitosan powder; wherein the concentration of nano-TiO2 powder in the tannin chitosan solution is 0.5 g / L;
[0035] (4) 8 g of titanium-modified tannin chitosan, 1 g of chlorhexidine, 1 g of sodium hexametaphosphate and 90 g of water were placed in a stirring tank in sequence and stirred at room temperature for 2 to 3 hours to obtain a high-efficiency sludge conditioner.
[0036] Example 2
[0037] The method for treating organic biochemical sludge with the sludge conditioner prepared in Example 1 is specifically as follows:
[0038] 1. Sludge conditioning
[0039] The pH value, absolute dry sludge content and moisture content of the original sludge are determined, and the sludge conditioner is added according to the amount of absolute dry sludge. During conditioning (after adding the conditioner), the rotation speed is 200-500rpm and the conditioning time is 3-5min.
[0040] 2. Capillary absorption time determination
[0041] At present, the CST-2 capillary absorption time meter is used to measure the wetting time (in theory, the shorter the CST time, the better the hydrophobicity of the conditioned sludge, the better the mud-water separation effect during the filter press, and the lower the moisture content of the mud cake formed after dehydration), and the dosage of the conditioning agent with the shortest CST time is selected for subsequent experiments.
[0042] 3. Plate and frame filter press
[0043] A small plate and frame filter press was selected for filtration, and the filter cloth was 750B polypropylene filter cloth (filtration accuracy 10μm). The parameters were set as follows: tightening pressure ≥ 20MPa, feed air pressure 6-7kg, feed time 2h, diaphragm mud pressure 1.5-2.0MPa, and pressing time 1h for sludge pressing.
[0044] 4. Parameter determination
[0045] Observe the appearance of the dewatered mud cake, which must fill the frame (at least ≥50g of absolutely dry sludge) and have uniform thickness around the mud cake;
[0046] Use a rapid moisture meter to measure the absolute dry sludge content of the mud cake and convert it to moisture content;
[0047] Record the amount of sludge fed into the filter press and calculate the feed rate of the pilot plate and frame filter press based on the absolute dry content of the original sludge.
[0048] The water quality indicators of the treated organic biochemical sludge are shown in Table 1.
[0049] Table 1
[0050]
[0051] Comparative Example 1
[0052] The treatment steps of Comparative Example 1 and Example 2 are basically the same, with the only difference being that the conditioning agent used in Comparative Example 1 is a traditional inorganic conditioning agent, namely slaked lime + ferric chloride (slaked lime is in solid form when added and is insoluble in water, and ferric chloride is first prepared into a 30wt% solution and then added) to treat the organic biochemical sludge.
[0053] Parameter determination
[0054] Observe the appearance of the dewatered mud cake, which must fill the frame (at least ≥50g of absolutely dry sludge) and have uniform thickness around the mud cake;
[0055] Use a rapid moisture meter to measure the absolute dry sludge content of the mud cake and convert it to moisture content;
[0056] Record the amount of sludge fed into the filter press, and calculate the feed rate of the small test plate and frame filter press based on the absolute dry content of the original sludge;
[0057] Inductively coupled plasma atomic emission spectrometry was used to test the corrosive ion concentrations of the sludge filtrate, including iron, chloride, and chlorine ions.
[0058] The water quality indicators of the treated organic biochemical sludge are shown in Table 2.
[0059] Table 2
[0060]
[0061] By comparing Tables 1 and 2, it can be seen that the dosage of the sludge conditioner of the present invention is 6.1% of that of the traditional inorganic conditioner (the total dosage of ferric chloride plus slaked lime is 49.2wt% of the sludge solid content, while the dosage of the sludge conditioner of the present invention is 3wt% of the sludge solid content). In addition, the dehydration effect and absolute dry mud feeding rate of the sludge conditioner of the present invention on organic biochemical sludge are better than those of the traditional inorganic conditioner, the dehydration rate is reduced by 23.15%, the absolute dry mud feeding rate is increased by 34.33%, and the corrosive ion concentration of the sludge filtrate is reduced by 68.37%.
[0062] Comparative Example 2
[0063] The treatment steps of Comparative Example 2 are basically the same as those of Example 2, with the only difference being that the conditioning agent used in Comparative Example 2 is a traditional organic conditioning agent, namely PAM, to treat the organic biochemical sludge.
[0064] Parameter determination
[0065] Observe the appearance of the dewatered mud cake, which must fill the frame (at least ≥50g of absolutely dry sludge) and have uniform thickness around the mud cake;
[0066] Use a rapid moisture meter to measure the absolute dry sludge content of the mud cake and convert it to moisture content;
[0067] Record the amount of sludge fed into the filter press, and calculate the feed rate of the small test plate and frame filter press based on the absolute dry content of the original sludge;
[0068] Inductively coupled plasma atomic emission spectrometry was used to test the corrosive ion concentrations of the sludge filtrate, including iron, chloride, and chlorine ions.
[0069] The water quality indicators of the treated organic biochemical sludge are shown in Table 3:
[0070] Table 3
[0071]
[0072] By comparing Table 1 and Table 3, it can be seen that the dosage of the sludge conditioner of the present invention is 60% of that of the traditional organic conditioner. In addition, compared with the traditional organic conditioner, the sludge conditioner of the present invention reduces the dehydration rate of organic biochemical sludge by 24.72% and increases the absolute dry sludge feeding rate by 15.65%.
[0073] The sludge conditioner of the present invention can reduce the moisture content of the treated sludge to below 55% by using Sanisol to release bacterial intracellular water and bacterial interstitial water, sodium hexametaphosphate to release EPS bound water, and titanium-modified tannin chitosan to adsorb the dispersed sludge particles, which is significantly reduced by about 25% compared with the sludge moisture content after the use of organic sludge conditioners, and does not have the risk of secondary pollution. At the same time, compared with inorganic sludge conditioners, the sludge conditioner of the present invention does not contain corrosive ions such as chloride ions, trivalent iron, and aluminum ions, and will not increase the corrosive ion concentration of the sludge filtrate, thereby avoiding equipment corrosion, poor resource performance of sludge after dehydration, soil compaction after landfill, and salinization.
[0074] Comparative Example 3
[0075] The preparation method of the sludge conditioner of Comparative Example 3 is basically the same as that of Example 1, except that the titanium-modified tannin chitosan is replaced by tannin chitosan that is not titanium-modified. The specific steps are as follows:
[0076] (1) Preparation of tannin chitosan:
[0077] (1.1) Dissolve 0.2 g of chitosan in 50 mL of 0.5 M acetic acid, place in a stirring vessel and slowly stir at room temperature for 10 to 15 min until uniform;
[0078] (1.2) Add 30 wt% sodium hydroxide to the solution of step (1.1) and adjust the pH to 6-7; adjust the temperature of the stirred tank to 65-70°C, and continuously add 0.3 g of benzaldehyde dropwise thereto and react for 2-3 hours;
[0079] (1.3) The solution of step (1.2) was placed in an oven at 45°C and dried to obtain a solid powder, which was redispersed in water, to which 0.2 g of tannin was added, and the mixture was placed in a stirring kettle and slowly stirred at room temperature for 10 to 15 minutes until uniform;
[0080] (1.4) Add 0.3 g of glyoxal to the stirred tank, adjust the temperature of the stirred tank to 65-70°C, and react for 2-3 hours;
[0081] (1.5) placing the solution of step (1.4) in a 45°C oven and drying to obtain a solid powder, and then soaking the solid powder in 5 mL of 30 wt% hydrochloric acid for 5 to 8 h;
[0082] (1.6) placing the solution of step (1.5) in an oven at 45°C and drying for 24 hours to obtain powdered tannin chitosan;
[0083] (2) dissolving tannin chitosan in water to obtain a tannin chitosan solution with a concentration of 0.1 g / L;
[0084] (3) 8 g of 0.1 g / L tannin chitosan solution, 1 g of chlorhexidine, 1 g of sodium hexametaphosphate and 90 g of water were placed in a stirring tank in sequence and stirred at room temperature for 2 to 3 hours to obtain a sludge conditioner.
[0085] Subsequently, the treatment steps were basically the same as those in Example 2, and the organic biochemical sludge was treated with the sludge conditioner of Comparative Example 3.
[0086] Parameter determination
[0087] Observe the appearance of the dewatered mud cake, which must fill the frame (at least ≥50g of absolutely dry sludge) and have uniform thickness around the mud cake;
[0088] Use a rapid moisture meter to measure the absolute dry sludge content of the mud cake and convert it to moisture content;
[0089] Record the amount of sludge fed into the filter press, and calculate the feed rate of the small test plate and frame filter press based on the absolute dry content of the original sludge;
[0090] Inductively coupled plasma atomic emission spectrometry was used to test the corrosive ion concentrations of the sludge filtrate, including iron, chloride, and chlorine.
[0091] The water quality indicators of the treated organic biochemical sludge are shown in Table 4:
[0092] Table 4
[0093]
[0094] It can be seen from Table 1 and Table 4 that, compared with Example 1, the dosage of the sludge conditioner in Comparative Example 3 increased by 33.33%, the dehydration effect on the organic biochemical sludge decreased by 10%, and the absolute dry sludge feeding rate decreased by 17.21%.
[0095] Comparative Example 4
[0096] The preparation method of the sludge conditioner of Comparative Example 4 is basically the same as that of Example 1, except that the titanium-modified tannin chitosan is replaced by titanium-modified chitosan. The specific steps are as follows:
[0097] (1) dispersing chitosan in water to obtain a chitosan dispersion with a concentration of 0.1 g / L;
[0098] (2) adding nano-TiO2 powder to chitosan dispersion, and after ultrasonic dispersion for 30 minutes, placing the mixture in a muffle furnace and reacting at 170° C. for 1.5 hours to obtain titanium-modified chitosan powder; wherein the concentration of nano-TiO2 powder in the chitosan dispersion is 0.5 g / L;
[0099] (3) 8 g of titanium-modified chitosan, 1 g of chlorhexidine, 1 g of sodium hexametaphosphate and 90 g of water were placed in a stirring tank in sequence and stirred at room temperature for 2 to 3 hours to obtain a sludge conditioner.
[0100] Subsequently, the treatment steps were basically the same as those in Example 2, and the sludge conditioner of Comparative Example 4 was used to treat the organic biochemical sludge.
[0101] Parameter determination
[0102] Observe the appearance of the dewatered mud cake, which must fill the frame (at least ≥50g of absolutely dry sludge) and have uniform thickness around the mud cake;
[0103] Use a rapid moisture meter to measure the absolute dry sludge content of the mud cake and convert it to moisture content;
[0104] Record the amount of sludge fed into the filter press, and calculate the feed rate of the small test plate and frame filter press based on the absolute dry content of the original sludge;
[0105] Inductively coupled plasma atomic emission spectrometry was used to test the corrosive ion concentrations of the sludge filtrate, including iron, chloride, and chlorine ions.
[0106] The water quality indicators of the treated organic biochemical sludge are shown in Table 5:
[0107] Table 5
[0108]
[0109] It can be seen from Table 1 and Table 5 that, compared with Example 1, the dosage of the sludge conditioner in Comparative Example 4 increased by 100%, the dehydration effect on the organic biochemical sludge decreased by 13.33%, and the absolute dry sludge feeding rate increased by 8.79%.
[0110] The sludge conditioner of the present invention is added into concentrated sludge. The chlorhexidine in the agent can release the bacterial intracellular water in the sludge by changing the permeability of the cell membrane and denaturing the protein on the bacterial cell wall and the cell membrane, and at the same time can effectively weaken the adhesion between the bacteria and EPS; the sodium hexametaphosphate in the agent can effectively destroy the EPS structure and release the bound water through the mechanisms of chelation, promoting the hydrolysis of polysaccharides and proteins, changing the surface charge of EPS and physical destruction, thereby changing the morphology of sludge flocs. Since there are abundant active amino and hydroxyl groups on the surface of chitosan, the chemical structure of chitosan can be changed by tannin amination of these free amino groups, converting it into tannin chitosan, which can effectively improve the solubility of chitosan and increase the number of active groups such as polyphenol hydroxyl and carboxyl groups on the molecular chain. The generated polymer has a branched structure, disperses the flocculation groups, and has a stronger adsorption and electrical neutralization effect and adsorption bridging effect on the sludge. At the same time, loading titanium salt on the tannin-treated chitosan can improve the sedimentation performance of cationic chitosan as a flocculant, and the sludge after flocculation and precipitation can be calcined at high temperature to regain TiO2 with high photocatalytic activity.
Claims
1. A sludge conditioner, characterized in that: The invention comprises the following components in parts by weight: 0.5 to 1 part of benzalkonium bromide, 0.5 to 1 part of sodium hexametaphosphate, 5 to 10 parts of titanium-modified tannin chitosan and 88 to 95 parts of water.
2. The sludge conditioner according to claim 1, characterized in that: The titanium modified tannin chitosan is prepared by the following method: TiO2 nanoparticles are mixed with tannin chitosan solution, and the mixture is uniformly mixed and then calcined at high temperature to obtain the titanium modified tannin chitosan.
3. The sludge conditioner according to claim 2, characterized in that: The concentration of the tannin chitosan solution is 0.05-0.2 g / L; in the tannin chitosan solution, the concentration of the TiO2 nanoparticles is 0.1-1.0 g / L.
4. The sludge conditioner according to claim 2, characterized in that: The high temperature calcination temperature is 160-180°C, and the reaction time is 1-2h.
5. The sludge conditioner according to claim 2, characterized in that Tannin chitosan is prepared by the following method, and the method steps are as follows: (1) Dissolve chitosan in acetic acid, stir evenly and adjust the pH to 6-7; (2) adding benzaldehyde dropwise to the solution of step (1) at high temperature to carry out a reaction; (3) dispersing the reaction product in water, adding tannin thereto, and mixing uniformly; (4) adding glyoxal dropwise to the mixed solution of step (3) at high temperature to carry out a reaction; (5) Soaking the product after the reaction in hydrochloric acid, and drying after soaking to obtain tannin chitosan.
6. The sludge conditioner according to claim 5, characterized in that: In step (2) and step (4), the reaction temperature is 65-70° C. and the reaction time is 2-3 h.
7. The sludge conditioner according to claim 5, characterized in that: In step (3), the mass ratio of chitosan to tannin added is 1:1 to 1.
5.
8. The sludge conditioner according to claim 5, characterized in that: In step (2) and step (4), the mass ratio of benzaldehyde to chitosan added is 1.5-2:1; the mass ratio of glyoxal to chitosan added is 1.5-2:
1.
9. The sludge conditioner according to claim 5, characterized in that: In step (5), the drying temperature is 45 to 50° C. and the drying time is 22 to 24 hours.
10. Use of the sludge conditioner according to claim 1 in treating organic biochemical sludge.
Citation Information
Patent Citations
Environment-friendly tannin-chitosan-based adhesive
CN110452635A
Sewage treatment agent and preparation method and applications thereof
CN110563162A
Tannic acid compounded polyacrylamide efficient sludge conditioner and application thereof
CN116161848A
Preparation method and application of tannin chemically derived heterogeneous nano zero-valent iron catalyst
CN116212952A
Urban domestic sewage and sludge treatment method and organic green manure
CN119019201A